Dividend Policy and Capital Market Theory - Bar-Yosef, Sasson; Kolodny, Richard (The Review of Economics and Statistics, 1976)
THE reaction of investors to the dividend policy of the firm has received considerable attention during the last two decades. During this period two principal schools of thought emerged. The first, led by Myron Gordon (1959, 1962), suggested that dividend policy is relevant to security valuation; the second, led by Modigliani and Miller (1961), suggested that it is not. Although the lines between these two positions were drawn more than ten years ago, the issue concerning dividend relevance remains unresolved today.' The reason for the long duration of the controversy is the lack of unambiguous empirical evidence which strongly supports either of the two schools.2 During the last decade the research on capital markets conducted by Sharpe (1964), Lintner (1965), and Mossin (1966) brought to the field of finance the Capital Asset Pricing Model (hereafter, CAPM). This valuation model has provided the basis for a significant number of empirical studies ranging from the value of added disclosure requirements to the benefits of corporate mergers.3 Although it is customary in these studies to state the assumptions under which the CAPM was developed, the use of the model itself assumes implicitly that the degree to which the assumptions abstract from reality does not impair the model's usefulness as a testing device. One of the inherent assumptions in the use of CAPM concerns dividend policy. In this regard, using the CAPM implicitly assumes the irrelevance hypothesis indicating a strong tendency among scholars to accept the irrelevance position. The argument for this position initially spelled out by Modigliani and Miller (1958) is demonstrated through an analysis of (1) the rationality of the behavior of stockholders, and (2) market forces. It suggests that, as long as a firm's investment decisions are known, the capital market will evaluate the firm's shares according to its potential profitability. If certain shareholders prefer more cash income than dividends paid, they can obtain such by liquidating part of their stock holdings. Doing this, these investors would realize the same return as those who maintain their original stock holdings regardless of the firm's dividend policy.4 Contrary to this, the relevance school suggests that a payment of cash dividends by the firm to its shareholders has a significant impact on the valuation of its securities.5 The arguments set forth in support of this position vary from the informational content of dividends to the clientele effect and return prospects on retained earnings.6 The purpose of this paper is to present the results of a theoretical and empirical investigation of the dividend issue and to examine the implications of the findings in light of recent developments in capital market theory. The results of this study indicate, contrary to other recent studies,7 that investors do in fact have a net preference for dividends and, consequently, the practical use of the capital asset pricing model, which implicitly assumes investor indifference between returns in the form